Assessing motivational factors influencing effective learning among UiTM Negeri Sembilan science students / Farrah Nadia Baharuddin, Shahira Ariffin and Tengku Sharifeleani Ratul Maknu Tengku Sulaiman - Baharuddin, Farrah Nadia; Ariffin, Shahira; Tengku Sulaiman, Tengku Sharifeleani Ratul Maknu (Research Management Institute (RMI), 2012)
Motivation is a very interesting topic because it has great influence on education and learning. It can be regarded as the key to acquire new knowledge. Due to its importance, motivation has been the centre of focus for research for decades. However, graduates quality have been deteriorating as they only engage in surface learning as opposed to deep learning. Their learning process is more towards getting by or just to pass examination. As a result, many students are unable to recall things they have learned in the recent past. Thus, effective learning needs to take place as to encourage the students to be able to more analytical, conduct critical thinking and communicate their thoughts effectively. Thus, the research has two objectives namely to identify the important predictors that motivate students in attaining effective learning, to investigate to what extent the elements of social dimension as well as mental dimension and their ability to explain in attaining affective learning. There are several key items such as the data collection method, data sources as well as sampling design, which will be clarified in research methodology. This study will include a set of questionnaires that will be distributed among students in private and public institutions. As such, it hopes that this research will gain further knowledge on impact of students' motivation towards effective learning and subsequently manifested with academic excellence.